Attraversamento di luoghi simbolici. Petrarca, il bosco e la poesia Con testimonianze sull'autrice - Noferi, Adelia (Biblioteca di Studi di Filologia Moderna, 2021)
Adelia Noferi (1922-2014) was one the greatest scholars of Petrarch, Bruno, and D'Annunzio and twentieth-century poetry, as well as one of the most refined theorists of the twentieth century and its poetics. This book collects previously unpublished texts, some of which arose from the courses that Noferi taught at university; they reflect with a wealth of doctrine and suggestions on poetry and criticism through Petrarchan readings and an adventurous journey through the topoi of the forest in literature. From the locus amoenus to the labyrinth, the investigation takes place at a structural, formal, symbolic and cultural level and retraces forms and junctions of the imagination through exemplary texts (from Dante to Bigongiari and Zanzotto). The second section, enriched by an iconographic apparatus, collects profiles and testimonies in multiple voices, a biography between generations, and a complete bibliography.